Developing Next-Generation Engineers -. IMPACTS - Lachlan MacKinnon (2007)
In the development of remote labs and virtual engineering tools the focus has rightly been on the technical challenges to be overcome to provide useful and usable tools and experimentation. However, the utilization of such facilities in educational settings is not simply a case of making students and faculty aware of their existence. In fact, there are significant pedagogical issues in the blending of remote and virtual facilities with cohort and location-based teaching and learning, and a number of research findings have highlighted student issues with both traditional teaching methods and the use of predominantly on-line materials. The authors have considerable experience in the development, production and use of eLearning materials in academic and industrial environments, and in tool virtualization and remote labs, and here propose a model for a distributed Masters program that supports students on a location-neutral basis utilizing online eLearning materials, virtual tools and remote lab facilities, combined with location-specific specialist teaching and learning facilities. The program described is already in operation between three European Universities, with the intention to expand both within Europe and beyond, utilizing the Erasmus Mundus scheme. The program is based on a constructivist pedagogic model that demands considerable independence of study and research on the part of the students, within a rich environment of high-quality specialist materials offered in a wide variety of modes. The authors believe that this approach optimizes the benefits of individual academic specialization in research and teaching, combined with effective use of eLearning materials, remote labs and virtual tools in a distributed environment, and thereby addresses a number of the issues identified from the research while also offering a high quality program to educate and develop next generation Engineers.